Caracterização de polpas e bebidas à base de extrato hidrossolúvel de soja, amora, pitanga e mirtilo: análises reológicas, fitoquímicas, físico-químicas, microbiológicas e sensoriais - Gazola, Marcos Bertani (2013)
The Brazilian geography and its continental dimensions make the country suitable for cultivation and growth of different plant species, occupying the ranking of third largest world producer of fruits and the second of soybean. Global trends point to the growing market of non-alcoholic beverages, particularly, the ones with fruits and soybean water extracts base. Before these facts, this research sought the characterization of pulps and beverages of pitanga (Eugenia uniflora L.), mulberry (Morus nigra) and blueberry (Vaccinium spp.), from commercial plantations and the biome Araucaria Forest in the southwest of Parana, through the physico-chemical, microbiological, rheological, phytochemical, anti-microbiological and sensory analysis. Among the physico-chemical analysis of mineral content, protein, solids, lipids and carbohydrates, the pH and the relation total soluble solids/ total tritable acidity (SS/ATT) were the descriptor that best explained the difference between pulps and beverages (Principal Component Analysis). The phytochemical prospection in the extract of the fruits’ pulps revealed the presence of several secondary metabolites, mainly flavones, flavonols, xanthones and flavanonols. The polar extract presented higher richness of these constituents. The extracts were also analyzed through infrared, allowing the observation that ethanol 70% is the most suitable solvent in antioxidants search, compared with petroleum ether and ethyl ether, because of its greater potential for polar groups extraction and the presence of O-H absorption peaks in all pulps. There was not statistic differences (p  0,05) in the antioxidants capacities of the pulps, however, the highest total phenolics obtained occurred in the mulberry pulp. The antimicrobiological activity tests indicated fungus power of the blueberry pulp for the Cândida tropicalis yeast, with minimum inhibitory concentration of 833,33 μg mL-1. The flow curves demonstrated a non Newtonian behavior with pseudoplastic characteristics, with excellent adjust to the Ostwald-de-Waele model. The temperature effect on the viscosity of pulps was verified through the equation of Arrhenius sort and analyzed in relation to activation energy, which highest value was obtained for the mulberry pulp. The sensory analysis of the prepared beverages pointed to the acceptability of the tasters, indicating potential to industrialization.